Prevalence of abnormal glucose tolerance and risk factors in urban and rural malaysia - Mustafa, N.; Kamarudin, N.A.; Ismail, A.A.; Khir, A.S.; Ismail, I.S.; Musa, K.I.; Kadir, K.A.; Yaacob, N.A.; Ali, O.; Harnida, S.; Bebakar, W.M.W.; Mohamud, W.N.W. (2011)
OBJECTIVE-To determine the prevalence of prediabetes and diabetes among rural and urban Malaysians. RESEARCH DESIGN AND METHODS-This cross-sectional survey was conducted among 3,879 Malaysian adults (1,335 men and 2,544 women). All subjects underwent the 75-g oral glucose tolerance test (OGTT). RESULTS-The overall prevalence of prediabetes was 22.1 (30.2 in men and 69.8 in women). Isolated impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) were found in 3.4 and 16.1 of the study population, respectively, whereas 2.6 of the subjects had both IFG and IGT. Based on an OGTT, the prevalence of newly diagnosed type 2 diabetes was 12.6 (31.0 in men and 69.0 in women). The prediabetic subjects also had an increased prevalence of cardiovascular disease risk factors. CONCLUSIONS-The large proportion of undiagnosed cases of prediabetes and diabetes reflects the lack of public awareness of the disease.